Предмет: Алгебра,
автор: Bady18
хелп решите:)))))))))))
Приложения:
Ответы
Автор ответа:
0
3x (x - y) + 3y(x + y) =
= 3x^2 - 3xy + 3yx + 3y^2 =
= 3x^2 + 3y^2 =
= 3(x^2 + y^2)
= 3x^2 - 3xy + 3yx + 3y^2 =
= 3x^2 + 3y^2 =
= 3(x^2 + y^2)
Автор ответа:
0
3х(х-у)+3у(х-у)=
=(3х+3у)(х-у)=
=3(х+у)(х-у)=
=3(х^2-у^2)=
=3х^2-3у^2
=(3х+3у)(х-у)=
=3(х+у)(х-у)=
=3(х^2-у^2)=
=3х^2-3у^2
Похожие вопросы
Предмет: Русский язык,
автор: korotkaaevgenia24
Предмет: Физика,
автор: damirtorsin50
Предмет: Литература,
автор: temragalievamalika
Предмет: Алгебра,
автор: Catya1988